Intestinal bacterial flora of Mediterranean gilthead sea bream (Sparus aurata Linnaeus) as a novel source of natural surface active compounds. (21st December 2017) - Floris, Rosanna; Scanu, Giuseppe; Fois, Nicola; Rizzo, Carmen; Malavenda, Roberta; Spanò, Nunziacarla; Lo Giudice, Angelina
Abstract: Microbial communities play different functions in the digestive tract of fish and represent a source of bioactive compounds. This study was aimed to detect the presence of biosurfactant (BS)‐producing bacteria in the intestine of gilthead sea bream ( Sparus aurata L.) to select strains candidate for biotechnological applications in aquaculture. A total of 100 bacterial strains were isolated from the guts of three groups of fish and analysed by different qualitative screening tests and the tensiometric analysis. BSs were extracted, characterized by thin‐layer chromatography (TLC) and their antibacterial activity against bacterial pathogens of interest in aquaculture was determined. A total of 17 out of 100 strains, affiliated to the genera Pseudomonas (11 isolates), Acinetobacter (1 isolate), Sphingomonas (4 isolates) and Aeromonas (1 isolate), displayed a stable emulsion production with the E24 index from 0% to 44%, a surface tension reduction from 8.3 to 30 mN/m and 11 of them exhibited antibacterial activity against fish pathogens. The TLC analysis indicated that the intestinal BSs consisted of compounds ascribed to the class of glycolipids–rhamnolipids. This is the first study reporting on the isolation and selection of BS‐producing bacteria from fish gut, a natural novel source of surface active compounds with potential biotechnological applications in aquaculture.